2011
DOI: 10.2478/10004-1254-62-2011-2098
|View full text |Cite
|
Sign up to set email alerts
|

Association Between XRCC1 ARG399GLN and P53 ARG72PRO Polymorphisms and the Risk of Gastric and Colorectal Cancer in Turkish Population

Abstract: Gastric cancer is one of the most common cancers of the gastrointestinal system, and its overall fi ve-year survival rate is still 15 % to 20 %, as it can mostly be diagnosed at an advanced stage. On the other hand, although colorectal cancer has a rather good prognosis, mortality is one half that of the incidence. As carcinogenesis is believed to involve reactive radicals that cause DNA adduct formation, impaired repair activity, and weakened tumour suppression, it would help to understand the role of the pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…One study conducted in Canada reported XRCC1 Arg399Gln was an independent predictor for progression (Bewick et al, 2009), and another study showed a nonsignificant decreased risk of survival for breast cancer (Rodrigues et al, 2011). Similar results were found for the survival of non-small-cell lung cancer, colorectal cancer, gastric cancer and ovarian cancer (Khrunin et al, 2010;Engin et al, 2011;Tahara et al, 2011;Liao et al, 2012).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…One study conducted in Canada reported XRCC1 Arg399Gln was an independent predictor for progression (Bewick et al, 2009), and another study showed a nonsignificant decreased risk of survival for breast cancer (Rodrigues et al, 2011). Similar results were found for the survival of non-small-cell lung cancer, colorectal cancer, gastric cancer and ovarian cancer (Khrunin et al, 2010;Engin et al, 2011;Tahara et al, 2011;Liao et al, 2012).…”
Section: Discussionmentioning
confidence: 58%
“…The gene polymorphism in codon 399 may be related to DNA repair, and likely has an effect on protein function (Savas et al, 2004). Several studies have found an association of XRCC1-399 with the risk of various cancers, such as breast cancer, colorectal cancer, lung cancer, thyroid carcinoma, gastric cancer and breast cancer (Engin et al, 2011;Fard-Esfahani et al, 2011;Xu et al, 2011;Raabe et al, 2012;Zhao et al, 2012). Previous study showed an improved survival rate for breast cancer patients with XRCC1-399 Gln/Gln receiving chemotherapy (Bewick et al, 2009;Rodrigues et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Karkucak et al (2012) reported no association of XRCC1 gene Arg399Gln polymorphism in lung cancer risk. But variations between individuals, lacking DNA repair capacity in humans may be prone to risk of various cancers as reported by Hu et al (2011) in Glioma, gastric cancer by Engin et al (2011) and Kumar et al (2012) reported risk in Head and neck cancers.…”
Section: Introductionmentioning
confidence: 95%
“…However, Hsu et al (2015) found no significant association between XRCC1 gene polymorphisms and skin cancer risk, although in a case-control study, Zhu et al (2015) demonstrated that individuals carrying the Arg194Trp variation in this gene are more susceptible to prostate cancer. Several investigators have scrutinized the association between XRCC1 gene polymorphisms and gastric cancer risk, but their results have been inconsistent (Yan et al, 2009;Engin et al, 2011;Yuan et al, 2011;Karahalil et al, 2012;Pan et al, 2012;Wen et al, 2012). In Turkish populations, Engin et al (2011) and Karahalil et al (2012) found a statistically significant association between the XRCC1 Arg399Gln gene polymorphism and gastric cancer risk in Turkish populations.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have scrutinized the association between XRCC1 gene polymorphisms and gastric cancer risk, but their results have been inconsistent (Yan et al, 2009;Engin et al, 2011;Yuan et al, 2011;Karahalil et al, 2012;Pan et al, 2012;Wen et al, 2012). In Turkish populations, Engin et al (2011) and Karahalil et al (2012) found a statistically significant association between the XRCC1 Arg399Gln gene polymorphism and gastric cancer risk in Turkish populations. Wen et al (2012), Pan et al (2012), andYuan et al (2011) revealed a significant relationship between the Arg194Trp variant and susceptibility to this disease among Chinese individuals, while Yan et al (2009) reported that Arg399Gln and Arg194Trp sequence alterations have no effect, but the Arg280His polymorphism significantly increases gastric cancer risk.…”
Section: Discussionmentioning
confidence: 99%